2014
DOI: 10.1155/2014/106363
|View full text |Cite
|
Sign up to set email alerts
|

Partial Purification and Characterization of a Heat Stable α-Amylase from a Thermophilic Actinobacteria,Streptomycessp. MSC702

Abstract: A partial purification and biochemical characterization of the α-amylase from Streptomyces sp. MSC702 were carried out in this study. The optimum operational conditions for enzyme substrate reaction for amylolytic enzyme activity from the strain were evaluated. The optimum pH, temperature, and incubation period for assaying the enzyme were observed to be 5.0, 55°C, and 30 min, respectively. The extracellular extract was concentrated using ammonium sulfate precipitation. It was stable in the presence of metal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 31 publications
3
19
0
1
Order By: Relevance
“…Ca 2+ and Mg 2+ are reported to enhance enzyme activity by Goyal et al (2005); Ashger et al (2007) and Kiran and Chandra, (2008). In accordance to the findings of Burhan et al (2003) and Singh et al (2014), Ni 2+ and Zn 2+ almost inhibited the enzyme production while in the medium. Ba 2+ , Fe 2+ and Co 2+ showed a negative effect on enzyme production lowering the titres considerably.…”
Section: Effect Of Divalent Ionssupporting
confidence: 91%
See 1 more Smart Citation
“…Ca 2+ and Mg 2+ are reported to enhance enzyme activity by Goyal et al (2005); Ashger et al (2007) and Kiran and Chandra, (2008). In accordance to the findings of Burhan et al (2003) and Singh et al (2014), Ni 2+ and Zn 2+ almost inhibited the enzyme production while in the medium. Ba 2+ , Fe 2+ and Co 2+ showed a negative effect on enzyme production lowering the titres considerably.…”
Section: Effect Of Divalent Ionssupporting
confidence: 91%
“…4), which is significantly higher than others. Similarly, optimum incubation temperature of 50°C for an enhanced amylase production has been reported in studies by Kunamneni et al (2005), Hernández, (2006), Asgher et al (2007);Aygan et al (2008); Zohra and Ahmad, (2012) and Singh et al (2014). A decrease in enzyme activity i.e.…”
Section: Effect Of Temperaturesupporting
confidence: 59%
“…However, Pb 2+ inhibited the activity of the enzyme. Singh et al (2014) have also reported an inhibitory effect by Hg 2+ , Pb 2+ and Cu 2+ and attributed this inhibition by these ions on the enzyme activity to the presence of indole amino acids in the enzyme and also a reflection of competition between exogenous and protein associated cations. In the presence of CaCl2, the enzyme retained up to 87-89% activity at temperature range 30°C-40°C and 90-93% activity at temperature range of 50°C-60°C and 89-90% at 70°C.…”
Section: Discussionmentioning
confidence: 95%
“…Characterization and stabilization of purified enzymes under controlled optimum condition (pH and temperature) are key physiological factors to be considered for maximum enzyme activity and for applications in industries and the environment (Singh et al, 2014). The partially purified peroxidase showed a maximum activity at pH 4.5 and was relatively stable in the pH range between 4.0 and 5.5.…”
Section: Discussionmentioning
confidence: 99%
“…Purification fold of the ammonium sulfate precipitation followed by dialysis of crude enzymes ranged from 2.52-10.67. Singh et al (2014) reported that after ammonium sulfate precipitation and dialysis, amylase recovered 56.58% with 2.98-fold purification. Mageswari et al (2012) stated that purification fold of amylase from Pontibacillus chungwhensis strain P1 were 10.1 after ammonium sulfate precipitation and dialysis.…”
Section: Screening Of Amylase Producing Bacteria For Orange Juice Clamentioning
confidence: 99%